2017
DOI: 10.3390/su9030355
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility Motive Attribution by Service Employees in the Parcel Logistics Industry as a Moderator between CSR Perception and Organizational Effectiveness

Abstract: Abstract:With sustainability and corporate social responsibility (CSR) emerging as urgent issues in the logistics service industry, the effects of CSR on employee work behavior is receiving increasing attention. This study explores this issue by considering intrinsic and extrinsic CSR motive attributions as moderating variables between CSR perception and organizational commitment and organizational citizenship behavior. The results of a cross-sectional survey and hierarchical regression analyses of 241 survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 43 publications
6
45
0
Order By: Relevance
“…This study indicated that if employees perceive their organizations' CSR practices as inauthentic and too much strategic instead of genuinely trying to improve the society and the environment, the positive effect of CSR perceptions on voluntary pro‐environmental behavior would weaken. The results of these hypotheses are consistent with the findings of previous literature (Afsar et al, ; Donia et al, ; Lange & Washburn, ; Lee & Seo, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study indicated that if employees perceive their organizations' CSR practices as inauthentic and too much strategic instead of genuinely trying to improve the society and the environment, the positive effect of CSR perceptions on voluntary pro‐environmental behavior would weaken. The results of these hypotheses are consistent with the findings of previous literature (Afsar et al, ; Donia et al, ; Lange & Washburn, ; Lee & Seo, ).…”
Section: Discussionsupporting
confidence: 92%
“…Employees feel more connected to the organization, and their sense of purpose and meaningful existence aggravate further by being part of such a group (Lee & Seo, 2017). They also exert extra efforts that are not explicit part of their job descriptions to satisfy that higher purpose and meaningfulness.…”
Section: The Moderating Effect Of Csr Motive Attributionsmentioning
confidence: 99%
“…CSR to employees describe the employees self-evaluation and personal interpretations of the CSR activities performed in the organization [49]. This evaluation and perception shaped the employees attitudinal and behavioral reactions in the workplace [50]. CSR to employees means that the organization encourages the employees to participate in the voluntary activities and set different policies to develop their skills and careers.…”
Section: Csr To Employees and Creative Work Involvementmentioning
confidence: 99%
“…Institutionalist and constructivist assume that the international trade environment is essentially inhabited by self-centered agents [9]. Hence, through trade policies, policy makers design a trade environment where firms' individuality and society's collective pluralism are in balance to protect the sustainability and wellbeing of the global economy [10].…”
Section: The Dichotomy Between Policy Makers and Private Firmsmentioning
confidence: 99%
“…The Resolution requires national governments to establish controls over exporting strategic items or the raw materials that could be used for manufacturing weapons of mass destruction (WMD) [9]. As a consequence of the resolution, each national government institutes a trade policy called Strategic Trade Control System (STCS) on its commodities exporters [7].…”
Section: The Dichotomy Between Policy Makers and Private Firmsmentioning
confidence: 99%